Energy density functional methods for atomic nuclei - Schunck, Nicolas (IOP (Series). Release 6., 2019)
Energy density functional (EDF) approaches have become over the past twenty years a powerful framework to study the structure and reactions of atomic nuclei. This book gives an updated presentation of non-relativistic and covariant energy functionals, single- and multi-reference methods, and techniques to describe small- and large-amplitude collective motion or nuclei at high excitation energy. Edited by an expert in energy density functional theory, Dr Nicolas Schunck, alongside several experts within the field, this book provides a comprehensive and informative exploration of EDF methods. Detailed derivations, practical approaches, examples and figures are used throughout the book to give a coherent narrative of topics that have hitherto rarely been covered together.